Impact of morphometric and catchment variables on summer organic carbon richness in deep temperate lakes - Dunalska J. A. (Knowledge and Management of Aquatic Ecosystems, 2011)
The study lakes are located in north-eastern Poland, in the same physiographic system. These lakes were formed during the last glacial period. The lakes differed in morphometry, catchment size and environmental conditions. The study included deep, clear water lakes that stratify in summer. The results from multiple linear regression equations indicate that the morphometric and catchment variables may influence mainly the particulate fraction of OC during summer stratification. No significant correlation was found between the examined parameters and the quantity (DOC) or the carbon-specific absorbance (SUVA260) of the dissolved fraction. The most important factors which determine POC abundance in lakes are the maximum depth (zmax), length and development of shoreline (L, DL), catchment area to lake volume (CA/V), and stratification percentage (“% strat.”), as well as epilimnion bottom area to epilimnion volume (AE/VE). Thus, in the summer the quantity of OC in lakes, especially of POC, will be determined by the in-lake production and consumption processes. Low productivity can be easily maintained in deep, strongly stratified lakes, and therefore should be protected and high water quality should be preserved.